Genomic Dissection and Expression Profiling Revealed Functional Divergence in Triticum aestivum Leucine Rich Repeat Receptor Like Kinases (TaLRRKs) - Shumayla,; Sharma, Shailesh; Kumar, Rohit; Mendu, Venugopal; Singh, Kashmir; Upadhyay, Santosh K. (Frontiers in Plant Science, 2016)
The leucine rich repeat receptor like kinases (LRRK) constitute the largest subfamily of receptor like kinases (RLK), which play critical roles in plant development and stress responses. Herein, we identified 531 TaLRRK genes in Triticum aestivum (bread wheat), which were distributed throughout the A, B, and D sub-genomes and chromosomes. These were clustered into 233 homologous groups, which were mostly located on either homeologous chromosomes from various sub-genomes or in proximity on the same chromosome. A total of 255 paralogous genes were predicted which depicted the role of duplication events in expansion of this gene family. Majority of TaLRRKs consisted of trans-membrane region and localized on plasma-membrane. The TaLRRKs were further categorized into eight phylogenetic groups with numerous subgroups on the basis of sequence homology. The gene and protein structure in terms of exon/intron ratio, domains and motifs organization were found to be variably conserved across the different phylogenetic groups/subgroups, which indicated a potential divergence and neofunctionalization during evolution. High-throughput transcriptome data and quantitative real time PCR analyses in various developmental stages, and biotic and abiotic (heat, drought and salt) stresses provided insight into modus operandi of TaLRRKs during these conditions. Distinct expression of majority of stress responsive TaLRRKs homologous genes suggested their specified role in a particular condition. These results provided a comprehensive analysis of various characteristic features including functional divergence, which may provide the way for future functional characterization of this important gene family in bread wheat.